The anatomy of torture : a documentary history of Filartiga v. Pena Irala - Aceves, William J. (Martinus Nijhoff Publishers, 2007)
Victims of human rights abuses have filed civil lawsuits in US courts to seek redress for their injuries. This book seeks to promote accountability for violations of international law. It tells the story of Filartiga v Pena-Irala, one of the significant examples of human rights litigation in the United States.